Effectiveness of Holland Career Counseling to Improve Career Maturity of the Students in the Faith-Based Educational School - Fitriyah, Fitriyah; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This study aims to test the effectiveness of Holland career counseling to improve the career maturity of students at the Faith-Based Educational School in Pamekasan. The study design used was an experiment involving as many as 7 students was selected by purposive random sampling. Instruments used in this study were Career Maturity Inventory (CMI)-Form C. The results showed Holland career counseling effective to improve the career maturity of students. This study provides clarification on the effectiveness of handling the career maturity of students with Holland career counseling.